Pengaruh Islamic Corporate Goverance dan Intellectual Capital terhadap Kinerja Perusahaan Perbankan Syariah di Indonesia Periode 2014 – 2018 - Uswatun Hasanah (CV. Satria Jaya, 2023)
As an institution that operates based on sharia principles (syariah banking) which has different characteristics from other companies, namely in its performance. Sharia banking is required to work in accordance with sharia principles and sharia business ethics, namely through the implementation of Islamic corporate governance and the use of capital (intellectual capital). This research aims to 1) determine the influence of Islamic corporate governance on the performance of sharia banking companies in Indonesia using JDPS, RJDPS and JRDPS proxies; and 2) determine the influence of intellectual capital on sharia banking performance in Indonesia using the iB-VAIC proxy. The analytical method used in this research is Partial Least Square (PLS) Analysis. The sample used in this research was sharia banking companies in Indonesia for the 2014 - 2018 period with a total of 6 companies from 13 sharia banking companies in Indonesia. The sampling method used in determining the sample was purposive sampling. The results of this research show that ICG has a positive and significant effect on the performance of sharia banking companies in Indonesia. Meanwhile, IC has a positive and insignificant effect on sharia banking companies in Indonesia.